Intraventricular Hemorrhage in Children with COVID-19 Confirmed - Utari Gustiany G; Rahmi Lestari; Finny Fitry Yani (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background. The most common symptom of Coronavirus disease 2019 (COVID-19) caused by SARS-CoV-2 is respiratory symptoms. However, neurological symptoms in adult patients are increasingly being reported. In children, neurological symptoms of COVID-19 are still underreported. This case report was aimed to describe intraventricular hemorrhage in a child with Covid-19 infection. Case presentation. We report a case of a 15-year-old girl with intraventricular bleeding, which is one of the COVID-19 infection symptoms or a possible symptom of a multisystem inflammatory syndrome in children (MIS-C). Laboratory tests on the first day of treatment showed an increase in leukocytes and decreased lymphocytes. On the 6th day of treatment, the patient had worsening symptoms of consciousness and high fever. The results of laboratory examination showed a decrease in kidney function and an increase in D-dimer. Conclusion. Severe clinical manifestations of COVID-19 can be in the form of neurological manifestations, one of which is intraventricular hemorrhage.